Primary Joint Arthroplasty Surgery: Is the Risk of Major Bleeding Higher in Elderly Patients? A Retrospective Cohort Study (2016)
Background Increased risk of bleeding after major orthopedic surgery (MOS) has been widely documented in general population. However, this complication has not been studied in elderly patients. The purpose of this study is to determine whether the risk of major bleeding after MOS is higher in elderly patients, compared with those operated at a younger age. Methods This retrospective cohort study included total hip and total knee arthroplasty patients operated during 5 consecutive years. The main outcome was the occurrence of major bleeding. Patients with other causes of bleeding were excluded. Relative risks (RRs) and confidence intervals (CIs) were calculated, and a multivariate analysis was performed. Results A total of 1048 patients were included, 56% of patients were hip arthroplasties. At the time of surgery, 553 (53%) patients were older than 70 years. Patients aged >70 years showed an increased risk of major bleeding (RR: 2.42 [95% CI: 1.54-3.81]). For hip arthroplasty, the RR of bleeding was 2.61 (95%CI: 1.50-4.53) and 2.25 (95% CI: 1.03-4.94) for knee arthroplasty. After multivariate analysis, age was found to be independently associated with higher risk of major bleeding. Conclusion According to European Medicines Agency criteria, patients aged ?70 years are at a higher risk of major bleeding after MOS, result of a higher frequency of blood transfusions in this group of patients. Standardized protocols for blood transfusion in these patients are still required. © 2016 Elsevier Inc.